Corrosion behavior analyses of metallic membranes in hydrogen iodide environment for iodine-sulfur thermochemical cycle of hydrogen production. (14th June 2018) - Bhushan, Bharat; Goswami, Nitesh; Parida, S.C.; Rath, B.N.; Kumar, Sanjukta A.; Karki, V.; Bindal, R.C.; Kar, Soumitra
Abstract: HI decomposition in Iodine-Sulfur (IS) thermochemical process for hydrogen production is one of the critical steps, which suffers from low equilibrium conversion as well as highly corrosive environment. Corrosion-resistant metal membrane reactor is proposed to be a process intensification tool, which can enable efficient HI decomposition by enhancing the equilibrium conversion value. Here we report corrosion resistance studies on tantalum, niobium and palladium membranes, along with their comparative evaluation. Thin layer each of tantalum, palladium and niobium was coated on tubular alumina support of length 250 mm and 10 mm OD using DC sputter deposition technique. Small pieces of the coated tubes were subject to immersion coupon tests in HI-water environment (57 wt% HI in water) at a temperature of 125–130 °C under reflux environment, and simulated HI decomposition environment at 450 °C. The unexposed and exposed cut pieces were analyzed using scanning electron microscope (SEM), energy dispersive X-ray (EDX) and secondary ion mass spectrometer (SIMS). The extent of leaching of metal into liquid HI was quantified using inductively coupled plasma-mass spectrometer (ICP-MS). Findings confirmed that tantalum is the most resistant membrane material in HI environment (liquid and gas) followed by niobium and palladium. Highlights: Corrosion resistance studies of metal membranes carried out in liquid HI. Corrosion resistance studies of metal membranes carried out in gaseous HI. Leaching behavior of metal into liquid HI analyzed by ICPMS studies. Iodine percolation onto metal membrane matrix analyzed by SIMS studies. The trend in corrosion resistance behavior: Tantalum > Niobium > Palladium.